2017
DOI: 10.1038/onc.2017.179
|View full text |Cite
|
Sign up to set email alerts
|

Functional antagonism of β-arrestin isoforms balance IGF-1R expression and signalling with distinct cancer-related biological outcomes

Abstract: With very similar 3D structures, the widely expressed β-arrestin isoforms 1 and 2 play at times identical, distinct or even opposing roles in regulating various aspects of G protein-coupled receptors (GPCR) expression and signalling. Recent evidence recognizes the β-arrestin system as a key regulator of not only GPCRs, but also receptor tyrosine kinases, including the highly cancer relevant insulin-like growth factor type 1 receptor (IGF-1R). Binding of β-arrestin1 to IGF-1R leads to ligand-dependent degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 68 publications
0
53
0
Order By: Relevance
“…Likewise, the IGF-1R could activate downstream non-kinase signaling pathways in a kinase-independent manner by employing the signal transduction machinery traditionally known to be used by the GPCR (e.g., the GRK/β-arrestin system and G-proteins) [32,33]. Equally important, components of these non-canonical, kinase-independent pathways orchestrate feedback mechanisms controlling the IGF-1R expression, trafficking, and signaling [34][35][36].…”
Section: Role Of Igf-1r Signaling In the Pathogenesis Of Dm And Cancermentioning
confidence: 99%
“…Likewise, the IGF-1R could activate downstream non-kinase signaling pathways in a kinase-independent manner by employing the signal transduction machinery traditionally known to be used by the GPCR (e.g., the GRK/β-arrestin system and G-proteins) [32,33]. Equally important, components of these non-canonical, kinase-independent pathways orchestrate feedback mechanisms controlling the IGF-1R expression, trafficking, and signaling [34][35][36].…”
Section: Role Of Igf-1r Signaling In the Pathogenesis Of Dm And Cancermentioning
confidence: 99%
“…It has been reported that wild type 53 melanoma cells demonstrate enhanced growth suppression in response to Nutlin-3, suggesting p53 status as a potential biomarker identifying tumors responsive to p53-reactivation therapy [ 48 ]. Yet, wild-type p53 is not an absolute requirement as several studies identified mutant p53 cells responsive to Nutlin-3 treatment, and it is likely that p53-independent mechanisms also modulate the Nutlin-3 response [ 41 , 48 51 ]. The precise mechanisms orchestrating the response to Nutlin-3 are not fully recognized, however it is worth pointing out that Nutlin-3 not only stabilizes p53 but also triggers Mdm2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms orchestrating the response to Nutlin-3 are not fully recognized, however it is worth pointing out that Nutlin-3 not only stabilizes p53 but also triggers Mdm2 activity. As Mdm2 is a known ubiquitin ligase for several substrates other than p53, including IGF-1R, it is not surprising that Nutlin mediated Mdm2 activation alters diverse cellular functions such as cell proliferation, differentiation, migration and survival even in a p53- mutant or null background [ 35 , 48 51 ]. A possible scenario, currently under investigation in our laboratories, aiming to explain this variability of cellular responses, is that Mdm2 acts as a hub adjusting the duration, magnitude and subcellular compartmentalization of signaling complexes, which are then interpreted by the cells for appropriate proliferative, death or migratory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide mismatches due to single-nucleotide polymorphisms (SNP) located on either the target miRNA response element (Nicoloso et al 2010;Saridaki et al 2014) or on miRNA IEs (Króliczewski et al 2018) suffice to affect the function of the IE and can have clear biological consequences, such as increased risk for cancer. This is the case for the insulin-like growth factor-1 receptor (IGF1R) that promotes cancer cell growth and survival and is essential for malignant transformation by many classical cancer-related genes, such as TP53 and BRCA1 (Suleymanova et al 2017;Worrall et al 2017). The SNP rs28674628, located in the IGF1R 3 ′ UTR, associates with increased cancer risk and earlier age at diagnosis of breast cancer in Jewish Ashkenazi carriers of the 185delAG BRCA1 mutation (Gilam et al 2013).…”
Section: The Ies In Ncrnasmentioning
confidence: 99%